Easy monitoring and data record system of electric current detected by ACS712 affordable non-destructive electrical current sensor - Mona Berlian Sari; Lia Yuliantini; Hafizh Prihtiadi; Mitra Djamal (Department of Physics – Universitas Negeri Padang UNP, 2020)
Monitoring and data record system of electric current on the current conducting wire has been developed. Recently, the current measurement was conducted by electronic circuit configuration by adding the shunt resistance in the circuit configuration. Compare to the voltage measurement, the electric current measurement has several obstacle and sometimes dangerous, especially on the AC current measurement. This study offers the automation of electric current measurement using affordable and non-destructive ACS712 Hall effect sensor. Hall effect is the phenomena of charge flow deflection in the metal plate that is placed in the magnetic field. By using this sensor, it is possible to detect the AC and DC current on conducting wires. The output of the sensor voltage will be change based on the magnetic field obtained due to current flows in the wire. Those output voltage are processed in microprocessor of ATMEGA238. Measurement results are saved in *.txt format. LabVIEW is used as the display system interface to simplify the utilization. The measurement is conducted in the Faraday cage. This system can be one of answer for the efficient and stable affordable current measurement with the precision is 0.9954 and average of accuracy percentage is 99.5934%. To reach those precision, the sensor calibration formula in datasheets should be corrected by subtracts the sensor calibration formula with the constant of 0.125.